FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MINAT KUNJUNGAN ULANG PELAYANAN ANTENATAL DI POLIKLINIK KEBIDANAN RSUD SYEKH YUSUF KAB. GOWA - Faiz Satrianegera; Jumriati Azis; M. Rusmin (Jurnal Kesehatan, 2020)
Antenatal care services provide pregnant women with standardised health services which include anamnesis, general and gestational assessments, indicator-induced laboratory assessments, as well as basic and specific intervention programs. This research aims to identify the factors influencing patient’s interest to revisit the antenatal care services provided by the Midwifery Polyclinic of Syekh Yusuf Public Regional Hospital in Gowa Regency. It uses descriptive quantitative method to investigate the issue. The samples consist of 91 respondents who are selected from a population of 178 respondents by using probability sampling technique. The research findings suggest that there is a correlation between the services (p= 0.002) and staffs of the polyclinic with respondents’ interest in revisiting the centre. However, the findings indicate that respondents’ knowledge (p= 0.628), attitude (p= 0.856), location (p= 0.004), the centre’s facilities (p= 0.384) and family support (p= 0.633) do not correlate with their interest in revisiting the Midwifery Polyclinic of Syekh Yusuf Public Regional Hospital. To conclude, this research recommends that the doctors and nurses of Midwifery Polyclinic of Syekh Yusuf Public Regional Hospital maintain their hospitality and precision to keep patients happy and comfortable so that they decide to revisit the centre